Diagnostic Value of Fractional Exhaled Nitric Oxide and Small Airway Function in Differentiating Cough-Variant Asthma from Typical Asthma - Yanqi Wang; Lixuan Zhao; Fang Chen; Yufeng Guo; Hongxia Ma; Baofen Han; Jiang Yi; Xiaomei Kong (Canadian Respiratory Journal)
Purpose. To explore the diagnostic value of fractional exhaled nitric oxide (FeNO), small airway function, and a combined of both in differentiating cough-variant asthma (CVA) from typical asthma (TA). Methods. A total of 206 asthma subjects, including 104 CVA and 102 TA, were tested for pulmonary function, bronchial provocation test and FeNO. The correlation between FeNO, small airway function and other pulmonary indicators was analyzed by single correlation and multiple regression analysis. The receiver operating characteristic (ROC) curve was established to evaluate the diagnostic efficiency of FeNO, small airway function, and their combination and to predict the optimal cut-off point. Results. All the respiratory function parameters and small airway function indicators in TA group were significantly different from those in CVA group, and FeNO value was significantly higher than that in CVA group. In addition, the area under the ROC curve (AUC) was estimated to be 0.660 for FeNO, 0.895 for MMEF75%/25%, 0.873 for FEF50%, 0.898 for FEF25%, 0.695 for Fres, 0.650 for R5-R20, and 0.645 for X5. The optimal cut-off points of FeNO, MMEF75%/25%, FEF50%, FEF25%, Fres, R5-R20 and X5, were 48.50 ppb, 60.02%, 63.46%, 45.26%, 16.63 Hz, 0.38 kPa·L−1·s−1, and −1.32, respectively. And the AUC of FeNO combined with small airway function indexes FEF25%, Fres, R5-R20, and X5 were prior than single indicators. Conclusion. FeNO and small airway function indexes might have great diagnostic value for differentiating CVA from TA. The combination of FeNO and FEF25%, Fres, R5-R20, and X5 provided a significantly better prediction than either alone.